Peptide-based biomaterials. Linking l-tyrosine and poly l-tyrosine to graphene oxide nanoribbons1. Issue 18 (14th May 2015) - González-Domínguez, J. M.; Gutiérrez, F. A.; Hernández-Ferrer, J.; Ansón-Casaos, A.; Rubianes, M. D.; Rivas, G.; Martínez, M. T.
<x xml:space="preserve">Abstract</x> GONRs grafted to tyrosine and poly-tyrosine can be used as biophysical tools for studying the oxidability of proteins or as fluorescent probes for detecting molecular or physical events.